PERENCANAAN KONSTRUKSI PENGENDALI SEDIMEN (CHEKDAM) DI HILIR KALI PACAL BOJONEGORO - Harjono, Harjono; Widhiastuti, Yulis (Universitas Semarang, 2018)
Meeting the needs and maintaining the availability of water is an effort where a situation where the area is usually not run by water such as settlements, industrial areas, and other public facilities. This situation is considered to be detrimental to both morally and materially, the impact of which will directly be felt by humans. Therefore humans must balance between needs and natural conditions.Please note that the Klepek Dam is one of the buildings that functions as a water reservoir after the Pacal Reservoir for irrigation needs in the rice fields. To realize the success of quality Dam buildings and able to function as planned, it is needed by making check dam using concrete consumption.From studies and calculations that have been done using software, AutoCad, and Harpes calculation methods, it is known the impact of flood discharge and cross section in the Lusi watershed to determine whether or not the cross section of the Pacal Reservoir is necessary. The problem of holding water in the Pacal Reservoir is overcome by making check dam using concrete consumption